Paradigmatic Shift in Pedagogical Design: Transforming Syllabus Development for Innovative Higher Education - BAKTIYAROVA, RAIGUL; Abdilda , Sholpan; Ismailova, Fariza (Pedagogy and Psychology, 2025)
The study addresses the problem of modernizing instructional practices in higher education by focusing on how instructors understand and apply pedagogical design in course and syllabus development. It emphasizes the shift from traditional approaches to innovative methods that incorporate digital resources, interactive strategies, and student-centered learning. Methodology and Methods. A mixed methodological framework was applied, combining surveys, semi-structured interviews, and content analysis of syllabi. Data were collected from instructors with diverse disciplinary backgrounds and teaching experience. The analysis focused on the formulation of learning outcomes, assessment strategies, and the integration of digital technologies. Results. The findings revealed that although instructors recognize the value of pedagogical design, they often lack systematic training and institutional support. Many syllabi displayed unclear or unmeasurable learning outcomes, limited use of varied assessment methods, and inconsistent incorporation of digital tools. These shortcomings indicate weak constructive alignment between objectives, teaching activities, and evaluation criteria. Scientific novelty. The study contributes new insights into the state of pedagogical design practices in higher education, particularly in relation to the integration of digital and interactive methods. It highlights the structural misalignments that hinder effective curriculum development and advances the understanding of pedagogical design as both a theoretical and practical framework. Practical significance. The research provides recommendations for improving professional development, strengthening methodological support, and investing in infrastructural resources. These measures can enhance the quality of course design, promote innovative teaching practices, and ensure greater coherence in aligning learning outcomes with instructional strategies.